Construction of an instrument designed to assess prosocial reasoning in children aged 7 to 8: a graphic version - Lemos, Viviana Noemí; CIIPME-CONICET; CIPCA-UAP (Pontificia Universidad Javeriana, 2010)
The aim of this study was to develop an instrument that would allow the assessment of prosocial thinking in children of 7 and 8 years of age. This work presents the procedures that were followed and the psychometric results of a version with pictographic support. A consistency was observed in the hierarchy of prosocial reasoning applied by children in each of the stories used in this instrument. The indexes of internal consistency were acceptable, based on the age of the children and the complexity of the construct being assessed. Results consistent with the theory were also found, as regards the relationship between the types of prosocial reasoning and the differences between sex and age, which support the construct validity of the instrument